Revision of the genus Lamprima Latreille, 1804 (Coleoptera: Lucanidae) - Reid, Chris A.m.; Smith, Kindi; Beatson, Max (Zootaxa, 2018)
The genus Lamprima Latreille, 1804 (Coleoptera: Lucanidae: Lampriminae: Lamprimini), is revised. Five species are recognised: one in New Guinea (L. adolphinae (Gestro, 1875)), two on isolated western Pacific islands (L. aenea Fabricius, 1792: Norfolk Island; L. insularis W.J. Macleay, 1885: Lord Howe Island), one in northeastern New South Wales (L. imberbis Carter, 1926) and a common widespread species in eastern and southern Australia, L. aurata Latreille, 1817.                   Lamprima aurata varies considerably morphologically and many of the different forms encompassed by this variation have been described as species. Our study of morphology does not support this classification. Therefore, Lamprima aurata is designated a senior synonym of the following 24 names: L. cuprea Latreille, 1817; L. latreillii W.S. MacLeay, 1819 (new synonym); L. pygmaea W.S. MacLeay, 1819 (new synonym); L. fulgida Boisduval, 1835; L. micardi Reiche, 1841 (new synonym); L. rutilans Erichson, 1842; L. splendens Erichson, 1842; L. viridis Erichson, 1842; L. nigricollis Hope in Westwood, 1845 (new synonym); L. purpurascens Hope in Westwood, 1845 (new synonym); L. sumptuosa Hope in Westwood, 1845 (new synonym); L. tasmaniae Hope in Westwood, 1845 (new synonym); L. varians Burmeister, 1847 (new synonym); L. cultridens Burmeister, 1847 (new synonym); L. amplicollis Thomson, 1862 (new synonym); L. krefftii W.J. MacLeay, 1871 (new synonym); L. violacea W.J. Macleay, 1885 (new synonym); L. mandibularis W.J. Macleay, 1885 (new synonym); L. sericea W..J Macleay, 1885 (new synonym); L.nigripennis W.J. Macleay, 1885 (new synonym); L. minima W.J. Macleay, 1885 (new synonym); L. mariae Lea, 1910; L. coerulea Boileau, 1913 (new synonym); L. insularis Boileau, 1913 (new synonym). Lamprima adolphinae is a senior synonym of L. bohni (Darge & Séguy, 1953) (new synonym). Lamprima schreibersi Hope in Westwood, 1845, is an unnecessary nomen novum for L. aenea redescribed by Schreibers in 1802 from the same material as Fabricius, and therefore an objective synonym of L. aenea. Lamprima puncticollis Dejean, 1833, L. coerulea Hope in Westwood, 1845, and L. insularis Hope in Westwood, 1845, are nomina nuda, the last two names first made available by Boileau in 1913. The five Lamprima species are redescribed and recommendations made for their conservation. Type specimens of the species of Lamprima described by William Sharpe MacLeay and William John Macleay are illustrated for the first time. Lectotypes are designated for Lamprima insularis, L. latreillii, L. latreillii sericea, and L. mandibularis.